Концептуальні основи ефективного впровадження методології Agile в системі управління процесами на підприємстві - Зубков, Артур Олегович; Zubkov, Artur Olegovich (Ірпінь, 2023)
Результати досліджень вказують на важливість узагальнення теоретичних засад застосування методології Agile в управлінні процесами на підприємстві та аргументуванні практичних рекомендацій щодо послідовності її впровадження в систему управління ПрАТ «Миронівський хлібопродукт». Обґрунтовано рекомендації щодо послідовності введення методології Agile в систему управління процесами агрохолдингу ПрАТ «Миронівський хлібопродукт».

The research results indicate the importance of summarizing the theoretical foundations of the application of the Agile methodology in the management of processes at the enterprise and arguing practical recommendations regarding the sequence of its implementation in the management system of PrJSC "Myronivskyi Hliboprodukt". The recommendations regarding the sequence of introducing the Agile methodology into the process management system of the agricultural holding PrJSC "Myronivskyi Hliboprodukt" are substantiated.
Conceptual foundations of effective implementation of Agile methodology in the process management system at the enterprise
Keywords: agile; гнучкі методи управління; Agile-методологія; ціннісно-орієнтований підхід; система управління підприємством; agile; flexible management methods; Agile-methodology; value-oriented approach; enterprise management system